Audit Oversight in the Context of the European Union - Monteiro, D.; Gaio, C.; Morais, A.; Laureano, Raul M. S. (8th EIASM Workshop on Accounting and Regulation, 2019)
The sequence of financial scandals at the beginning of the millennium, mainly due to the focus placed on the failures of auditors, considerably damaged the credibility of financial audit. Since then, governments and regulators have made several efforts in order to re- establish the confidence lost, mainly through regulation measures and its oversight. The recent European regulation in audit field, in effect since June 2016 in all member states, is also an attempt to recover the competence and independence of auditors, in particular, the perception of their credibility at the eyes of society. The main characteristic of these new rules is the substitution of the peer review system – in effect in several member states until the mentioned date – for an oversight conducted by an independent body, system which seems to configure the prevalence of the independence over the competence. Based on the new regulation, this research aims to identify which rules related with audit oversight are associated with a high level of audit quality in both dimensions: real quality and perceived quality, related with the Public Interest Entities, within the European Union. The research focused on both of these dimensions – real and perceived – and its measurement was based on the following proxies: the quality of financial information through earnings management and the impact of qualified opinions in financial costs. The results do not corroborate all the options taken by the European Union in the new regulation, once they are not positively associated with audit quality and they also consolidate the assumption that the balance between competence and independence is not the only challenge related to the oversight of the audit profession. In fact, the evidence demonstrates that the balance between the real and perceived quality is a relevant matter. In conclusion, the big challenge is to frame the aspects of inverse effect between real and perceived audit quality and how to keep them balanced, with the assurance of independence and competence of auditors.